Diseño de un sistema de contabilidad agropecuaria en la hacienda San Luis ubicada, en la parroquia Cusubamba, cantón Salcedo, provincia de Cotopaxi. - Caguana Liquinchana, Jenny Alexandra (2020)
The present integrative project has as a general objective the design of an Agricultural Accounting System for the San Luis Farm, located in the Cusubamba parish, in order to be able to meet the needs of internal control of all agricultural economic activities developed within the estate, allowing the owner to carry out measures in a more timely manner regarding the improvement of production. In order to know the real situation of the company, quantitative research was used, with a deductive approach, with the support of techniques and instruments of information collection, a documentary investigation was carried out helping in the process of search, compilation, analysis, criticism and interpretation of data from secondary sources and field research for the collection of direct data, through instruments such as the direct observation sheet, evidencing economic activities and the interview directed to the owner, the data collected were stored in different physical and digital media, to then to be analyzed, the same ones that allowed the realization of the approach, formulation of the problem and the justification of the objective of the project, with this we proceed to present the proposal for the design of an Agricultural Accounting System, making known the scope, delimitation of the project and the beneficiaries of it. For this purpose, several activities are planned and executed according to the specific objectives detailed in this document, the main ones being: The scientific technical foundation, giving theoretical support on agricultural accounting and related subjects; Determination of source documents within the production process through the financial diagnosis of the company, which facilitated obtaining documents from each stage of the process of agricultural accounting of the company; and the Accounting System approach supported by an accounting cycle, based on accounting standards such as NIC41, NIC16, NIIF for PYMES: Section 34, as a result, the financial statements could be structured according to the reality of the finance, which will allow controlling and making decisions . At the end, the analysis and discussion of the results are presented, detailing the technical, social and economic impacts and the recommendations for the project beneficiary.